Management of psoriasis in pregnancy. Issue 7605 (7th June 2007) - Weatherhead, Sophie; Robson, Stephen C; Reynolds, Nick J
Abstract : Many treatments for this chronic skin disease are harmful to the developing fetus, so careful pre-conception planning and management adjustment are crucial for the pregnant patient